PERLINDUNGAN DESAIN INDUSTRI KERAJINAN TANGAN TERHADAP USAHA KECIL MENENGAH MENURUT UU NO. 31 TAHUN 2000 - Roma Victoria; Ramli Siregar; Windha windha (TRANSPARENCY, 2013)
Protection of industrial design has many benefits for the perpetrators of Small and Medium Enterprises (SMEs). However, the implementation of the registration of industrial design rights are not fully reach the general public, especially people from small industries. It is very contradictory to remember that industrial design protection is an important part of the trading system. Issues raised in this paper is the design of industrial settings, protection against hand-crafted production of small and medium enterprises (SMEs), and industrial design an important role in overcoming the barriers experienced by small and medium enterprises (SMEs). The research method used in this study is descriptive, namely the research literature (Library Research) by collecting material - material from books, magazines, articles, internet, legislation danhasil other scholarly writings are closely related to the purposes of the preparation of the work This scientific.                The results of this study it can be concluded that the Protection of Industrial Design is necessary to protect the handicraft production of small and medium enterprises (SMEs) from losses incurred by its imitators and legal protection that would be obtained by Small and Medium Enterprises offender registration when the work is the exclusive right the crafts related to moral rights and economic rights granted to applicants in recognition of the intellectual work of a small to medium sized businesses. Protection of Industrial Designs for handicrafts will have many benefits for small medium businesses (SMBs). First, small and medium business actors can pursue his imitators prevention of making and selling copies of the original. Second, small and medium businesses can recover damages, either actual or legal advantages. Legal protection will be at the party to register for the work and have proof of registration certificate. Keywords: Desain Industri, Usaha Kecil Menengah.